Why Haven't You Published That Research (and Your Other Ideas)? - Florita S. Montgomery; LaRae M. Donnellan; Larry R. Whiting (Journal of Applied Communications, 1996)
Various disincentives and barriers keep communicators from pursuing scholarly publication opportunities.